A study of deprivation level, approval motive and locus of control as moderators of job satisfaction.[article]. - Kotia Brij Lata
aThe moderating effect of prolonged deprivation in terms of experiential input, approval motive as a motivational disposition and locus of control as a personality dimension on job satisfaction was investigated. One hundred seventy(170)male employees engaged in block level district administration constituted the sample of the present study. a 2x2x2 factorial design was used. The results of separate analysis of variance(ANOVA)revealed that prolonged deprivation, approval motive and locus of control have significant moderating effects on extrinsic job satisfaction and no significant effects were found on intrinsic job satisfaction and overall job satisfaction. -- (from the author)